AID, APOBEC3A and APOBEC3B efficiently deaminate deoxycytidines neighboring DNA damage induced by oxidation or alkylation - Diamond, Cody P.; Im, Junbum; Button, Erynn A.; Huebert, David N.G.; King, Justin J.; Borzooee, Faeze; Abdouni, Hala S.; Bacque, Lisa; McCarthy, Erin; Fifield, Heather; Berghuis, Lesley M.; Larijani, Mani (Biochimica et biophysica acta. General subjects, 2019)
AID/APOBEC3 (A3) enzymes instigate genomic mutations that are involved in immunity and cancer. Although they can deaminate any deoxycytidine (dC) to deoxyuridine (dU), each family member has a signature preference determined by nucleotides surrounding the target dC. This WRC (W = A/T, R = A/G) and YC (Y = T/C) hotspot preference is established for AID and A3A/A3B, respectively. Base alkylation and oxidation are two of the most common types of DNA damage induced environmentally or by chemotherapy. Here we examined the activity of AID, A3A and A3B on dCs neighboring such damaged bases. Substrates were designed to contain target dCs either in normal WRC/YC hotspots, or in oxidized/alkylated DNA motifs. AID, A3A and A3B were purified and deamination kinetics of each were compared between substrates containing damaged vs. normal motifs. All three enzymes efficiently deaminated dC when common damaged bases were present in the -2 or -1 positions. Strikingly, some damaged motifs supported comparable or higher catalytic efficiencies by AID, A3A and A3B than the WRC/YC motifs which are their most favored normal sequences. Based on the resolved interactions of AID, A3A and A3B with DNA, we modeled interactions with alkylated or oxidized bases. Corroborating the enzyme assay data, the surface regions that recognize normal bases are predicted to also interact robustly with oxidized and alkylated bases. AID, A3A and A3B can efficiently recognize and deaminate dC whose neighbouring nucleotides are damaged. Beyond AID/A3s initiating DNA damage, some forms of pre-existing damaged DNA can constitute favored targets of AID/A3s if encountered. •AID, APOBEC3A and APOBEC3B can act on certain damaged DNA sequences more efficiently than their most favored normal hotspots•AID, APOBEC3A and APOBEC3B can recognize and act on DNA that is damaged by environmental or chemotherapeutic agents•The DNA binding motifs on the surfaces of AID, APOBEC3A and APOBEC3B recognize specific damaged bases